(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
This article analyzes the problems that arise when trying to execute a judicial decision, issued by a Family Judge of First Instance or a judicial agreement with res judicata authority. The Civil Procedures Code in force in the State of Tabasco, in its articles 383 and 385 establish the forms of “FORCED EXECUTION” and “DIRECT EXECUTION”. Of which it is interpreted that direct execution is updated when the adversary of the party requesting execution does not necessarily have to intervene; interpreted a contrary sensu, the execution takes place when there is opposition by the opposing party. However, the procedure to be followed is not specified, especially when there is a party that opposes the execution; Therefore, in the absence of an express provision, the execution is followed through an incidental claim, in which the parties have to again submit to a trial, offer evidence, and release it, until the issuance of a judgment in which the authority again orders its fulfillment and that it is many times delayed. It is similar when in an informal resolution psychological therapies are ordered to the parties, and once it is raised to the category of res judicata, the filing of the procedure is ordered when it has been concluded; without following up on psychological therapies. Hence the importance of having an enforcement procedure in family matters, as well as an authority in charge of the procedure such as an enforcement court.